2001
DOI: 10.1046/j.1365-2249.2001.01423.x
|View full text |Cite
|
Sign up to set email alerts
|

Role of macrophage migration inhibitory factor (MIF) in murine antigen-induced arthritis: interaction with glucocorticoids

Abstract: SUMMARY(MIF) is a broad-spectrum proinflammatory cytokine implicated in human rheumatoid arthritis. The synthesis of MIF by synovial cells is stimulated by glucocorticoids, and previous studies suggest that MIF antagonizes the anti-inflammatory effects of glucocorticoids. This has not been established in a model of arthritis. We wished to test the hypothesis that MIF can act to reverse the anti-inflammatory effects of glucocorticoids in murine antigen-induced arthritis (AIA). Cutaneous DTH reactions and AIA we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
123
0
2

Year Published

2001
2001
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 126 publications
(130 citation statements)
references
References 26 publications
5
123
0
2
Order By: Relevance
“…The combination of effects on apoptosis and proliferation strongly suggest that MIF is a critical mediator of synovial hypercellularity in arthritis. Of note, MIF immunoneutralization in animal models of arthritis is associated with substantial reductions in synovial cellularity (11,12). In this study, very few proliferating cells were detected in mice with AIA synovitis, with no significant further reduction detectable in MIF -/-animals.…”
Section: Discussionmentioning
confidence: 50%
See 2 more Smart Citations
“…The combination of effects on apoptosis and proliferation strongly suggest that MIF is a critical mediator of synovial hypercellularity in arthritis. Of note, MIF immunoneutralization in animal models of arthritis is associated with substantial reductions in synovial cellularity (11,12). In this study, very few proliferating cells were detected in mice with AIA synovitis, with no significant further reduction detectable in MIF -/-animals.…”
Section: Discussionmentioning
confidence: 50%
“…AIA was induced and assessed in male mice (6-8 weeks) as described previously (12). Briefly, mice were injected subcutaneously with 200 g of methylated BSA (mBSA)/200 l of Freund's complete adjuvant (Sigma) and Bordetella pertussis (0.4 ϫ 10 9 organisms/400 l of saline per mouse; Difco, Detroit, MI) and received a subcutaneous boost of 200 g of mBSA/200 l of Freund's complete adjuvant on day 7.…”
Section: Induction Of Antigen-induced Arthritis (Aia)mentioning
confidence: 99%
See 1 more Smart Citation
“…Firstly, in experimental animal models of inflammatory arthritis, neutralisation of MIF markedly suppresses the inflammatory response. [5][6][7] Secondly, MIF protein within the synovial fluid of rheumatoid arthritis (RA) patients has been found to be elevated 5-to 10-fold higher than that seen in osteoarthritis patients and normal volunteers. 12 Thirdly, MIF is known to induce macrophage tumour necrosis factor a (TNFa) release and nitric oxide production, as well as being involved in T-cell activation, all of which play a role in RA pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Raised levels of MIF expression have been reported in RA serum and synovial fluid, and anti-MIF antibodies have been reported to delay the onset and severity of animal models of inflammatory arthritis. [5][6][7] Two functional promoter polymorphisms of the MIF gene have been described. Donn et al 8 identified a singlenucleotide polymorphism (SNP) in the 5' region of the MIF gene (MIF-173*G/C).…”
Section: Introductionmentioning
confidence: 99%